ALGORITHM OF PSYCHOLOGICAL SUPPORT OF PERSONNEL IN THE AREA OF MILITARY (COMBAT) OPERATIONS - Bespalko, A.; Lelyuk, M. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article is devoted to the issue of psychological support of personnel in the area of military (combat) operations. The article considers the approaches of various scientists to the definition of the concept of "psychological support", and describes its main elements and content. As a result of the theoretical overview of various scientific approaches to solving the problem of psychological support, it can be stated that psychological support is an effective tool for neutralizing a wide range of complex, unpredictable and dynamic destabilizing internal and external factors and is designed to work with different categories of citizens. The article proposes the main principles of psychological support of personnel, defines the main tasks and key spheres of personal influence. We consider psychological support within the general system of psychological support of the Armed Forces of Ukraine as a complete hierarchical structure that has a defined goal and task, a integrated methodical subordination. The technology of psychological support of personnel is based on typical life situations and problems that arise during direct participation in hostilities, age-related characteristics and ideas of psychological and socio-pedagogical support of the professional activities of military personnel. The terms and main stages of psychological support are determined, on the one hand, by the adaptation possibilities and peculiarities of mental processes of servicemen under conditions of excessive psychophysical stress caused by a hyperextreme situation, and on the other hand by the regulatory and legal support of the system of psychological support of the Armed Forces of Ukraine and the objective situation in certain theaters of war. The indicators of successful implementation of psychological support is the following development of personnel: personal readiness for learning and self-development; growth of volitional self-regulation and motivational readiness; adequate perception of reality; successful orientation in a dynamic environment; positive assessment of one’s own capabilities and confidence in positive final results; social activity, increasing confidence and trust in the immediate social environment; increasing self-esteem, reducing the level of anxiety and aggressiveness indicators; personal readiness to perform combat tasks.